Determinants of Chronic Energy Deficiency Among Pregnant Women in Keruak East Lombok: A Case-Control Study - Mutiara Rachmawati Suseno; Miftahurrizky Amelia; Fitra Arsy Nur Cory’ah (Yayasan Ahmad Mansyur Nasirah, 2026)
Chronic Energy Deficiency (CED) among pregnant women remains an important public health problem because it is associated with adverse maternal and neonatal outcomes, including anemia, low birth weight, and pregnancy complications. Keruak Primary Health Center reported one of the highest CED rates in East Lombok, with a prevalence of 13.67% in 2024. This study aimed to identify factors associated with CED among pregnant women in the working area of Keruak Primary Health Center, East Lombok. This quantitative analytical study used an unmatched case-control design based on secondary data from maternal health records from January to December 2024. The study population consisted of 1,117 pregnant women, and the sample included 338 respondents, comprising 169 pregnant women with CED and 169 pregnant women without CED selected using a 1:1 case-control ratio. Data were analyzed using chi-square tests and multivariate logistic regression. Bivariate analysis showed significant associations between CED and maternal education, parity, body mass index (BMI), frequency of antenatal care (ANC) visits, hemoglobin level, and iron tablet consumption. BMI in this study referred to the BMI recorded during pregnancy in the maternal health records. In the final multivariate model, BMI showed the strongest association with CED (OR=23.209; 95% CI: 8.463–63.651), followed by parity (OR=2.754; 95% CI: 1.554–4.880), hemoglobin level (OR=2.527; 95% CI: 1.385–4.612), and ANC attendance (OR=1.925; 95% CI: 1.027–3.609). These findings indicate that maternal nutritional status, parity, ANC utilization, and anemia are important factors associated with CED among pregnant women. Strengthening nutritional screening, preconception care, ANC follow-up, hemoglobin monitoring, iron-folic acid supplementation counseling, and targeted nutritional support may help improve early identification and management of pregnant women at risk of CED.